[Student Leaving VGs Cafe] - Juan Martinez::::::photographer::: (1980)
Student walking out of front entrance of VGs Cafe. This dining establishment was located between the Redbrick Dorms and the Sierra Madre/ Yosemite Dorm complex along the Grand Avenue entrance of campus across from the Performing Arts Center. The back of the photo lists Stephanie Arey as the woman pictured, freshman Aerospace Engineering major at the time.